Leucaena forage yield as influenced by soil conditioner and irrigation regime treatments - ALI E. SHARIEF, AHMED A. KANDIL, (Journal of Experimental Sciences)
Water is limiting factor of increasing cultivated lands, so water scarcity and drought stress, considered as one of the factors limiting agricultural forage production in the world. This can have achieved by increasing of cultivated pasture area or improving productivity of rangeland plants. Soil conditioners applied in these holes during cultivation and vigorous seedlings transported to this experimental site. Unvarying daily irrigation using a drip irrigation system. Applying poultry manure as soil conditioners in sandy soil twisted tallest shrubs, maximum values of a number of branches/plant, stem thickness and dry matter forage yield per plant and per hectare and uppermost values of water use efficiency at both summer and autumn cuts. Increasing drip irrigation discharges from 2, 4, 6 to 8 litres/h significantly produced the tallest plants, highest number of branches per plant, thickness of stem and dry forage yield/plant and per hectare as well as water use efficiency in both summer and autumn cuts. As regards to the interaction between soil conditioners and drip irrigation discharges on stem height, number of branches /plant, dry forage matter yield per plant and dry forage yield/ha. Applying poultry manure as soil conditioners in sandy soil and increasing discharges of drip irrigation by 8 litres/h significantly increased dry forage yield/ha.